Optimization of Transfusion Therapy in Peritonitis - Ye. V. Ryabikina; Ye. A. Chernogubova; V. M. Zhenilo; Z. I. Mikashinovich (Общая реаниматология, 2009)
Objective: to develop approaches to therapy for postoperative peritonitis on the basis of an analysis of changes into some indices of the kallikrein-kinin system, such as the key plasma proteolytic system and the blood proteinase potential, in this complication. Subjects and methods. The indices of the blood kallikrein-kinin system (the activities of kallikrein, a1-pro-teinase inhibitor, o^-macroglobulin, total arginine-esterase activity, and the level of prekallikrein) were determined in 22 patients diagnosed, as having postoperative peritonitis, before and after transfusion of the fresh frozen plasma (FFP) prepared in the standard fashion and from the donors intranasally receiving biolan in a daily dose of 3 mg within three days before blood donation. Results. The studies have shown that the patients with postoperative peritonitis have a drastic imbalance in the proteinase inhibitor system with a preponderance of the former. After FFP transfusion, a^-proteinase inhibitor and a^-macroglobulin deficiencies persist in patients with peritonitis, which is prognostically poor. Transfusion of the FFP taken from the donors taking biolan results in mobilization of the body’s adaptive and compensatory capacities and causes an increase in the blood antiproteinase potential. Conclusion. Dynamic imbalance between proteinases and their inhibitors is of considerable importance in the pathogenesis of postoperative peritonitis; the estimation of the serum activities of a^-proteinase inhibitor and fl^-macroglobulin may be used as informative criteria for a systemic inflammatory reaction and therapeutic effectiveness. Key words: postoperative peritonitis, kallikrein-kinin system, proteinases, inhibitors, biolan.